(untitled) (Eurasian Journal of Philology Science and Education, 2019)
The article analyzes the content of the recently published book «The Unknown in the Heritage of Mukhtar Auezov», which reflected unknown and littleknown materials, minutes of meetings, meetings of party and Soviet bodies concerning the personality of M.O. Auezov, decisions of the commissions, transcripts of the discussion of certain works of the writer. These materials make a tangible contribution to modern literary studies, literary history, give new impetus to the activities of scientists who have devoted their works to the works of M.O. Auezov. The article provides a review of these materials and typological characteristics in accordance with modern views and approaches.